Asset Misappropriation: a Fraud Hexagon Theory Perspective with Integrity as a Moderating Variable in the Public Sector (An Empirical Study of Regional Government Organizations in Jambi Province) - Rizqiyah, Wasiatur; Yudi, Yudi; Friyani, ⁠Rita (PT. Anagata Sembagi Education, 2026)
Fraud has become a critical issue that can threaten accountability and performance in the public sector. One common form of fraud is asset misappropriation, which has the potential to cause significant financial losses to the state. This study aims to examine the effect of the fraud hexagon on asset misappropriation, with integrity as a moderating variable, within Regional Government Organizations (OPD) in the Provincial Government of Jambi. The approach used was quantitative, with data collection techniques through questionnaires distributed to state civil servants. Data analysis was conducted using the Partial Least Square (PLS-SEM) method. The results showed that pressure and opportunity significantly influenced asset misappropriation, while rationalization, capability, arrogance, and collusion did not. These findings indicate that asset misappropriation in the local government sector is more influenced by pressure and opportunity than other factors. Furthermore, integrity was proven to weaken the influence of pressure on asset misappropriation, but was unable to moderate the influence of opportunity, rationalization, capability, arrogance, and collusion. These results confirm that integrity plays a role as a value-based internal control, but cannot replace the function of a strong internal control system. Therefore, efforts to prevent asset misappropriation need to be implemented by strengthening individual integrity and improving the effectiveness of internal control systems and organizational accountability. This research contributes to the development of the fraud hexagon theory in the context of the public sector in Indonesia.